Sleep apnea prevalence and severity after coronary revascularization versus no intervention: a systematic review & meta-analysis - Ajosenpää, Marjo; Sarin, Satu; Vahlberg, Tero; Ahlmen-Laiho, Ulla; Yüksel, Peker; Kalleinen, Nea; Toivonen, Jenni (Springer Science and Business Media LLC, 2025)
Purpose
Obstructive sleep apnea (OSA) is a common disease in patients with coronary artery disease (CAD). Approximately 40–80% of cardiovascular disease patients have obstructive sleep apnea. The manifestation of it can vary significantly in different types of CAD patients. This systematic review and meta-analysis investigate the prevalence and severity of OSA in patients with acute coronary syndrome (ACS).
Methods
This systematic review was conducted according to PRISMA guidelines. The first inclusion criteria were that a reliable sleep study had to be done after treating the patients’ acute coronary incident. All patients in the studies included were adults suffering from an ACS who underwent either coronary artery bypass grafting surgery (CABG), a percutaneous coronary intervention (PCI) or had no invasive coronary intervention done. A search was conducted within four valid databases 27.1.2023 and all suitable articles published after 1.1.2010 were included.
Results
Eight studies fulfilled the full inclusion criteria. In five of them, a sleep study had been performed after PCI, in two after no coronary intervention, and in one study after CABG. Mean AHI in no-OSA group after PCI was 9.5 /h (95% CI 5.3–13.7) and in the no intervention group 6.4 /h (95% CI 3.5–9.4). In OSA patients, mean AHI after PCI was 34.9 /h (95% CI 25.9–43.8) vs. 24.1 /h without intervention (95% CI 15.6–32.6).
Conclusions
Sleep apnea is very common among ACS patients and should be screened for and addressed after the acute coronary intervention. Moreover, we found that OSA is more severe in patients in whom PCI for ACS was indicated as opposed to patients who underwent no coronary intervention.